2020
DOI: 10.1007/s41109-020-00327-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of misinformation diffusion during a pandemic

Abstract: The role of misinformation diffusion during a pandemic is crucial. An aspect that requires particular attention in the analysis of misinfodemics is the rationale of the source of false information, in particular how the behavior of agents spreading misinformation through traditional communication outlets and social networks can influence the diffusion of the disease. We studied the process of false information transmission by malicious agents, in the context of a disease pandemic based on data for the COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…It was reported by a recent meta-analysis that the prevalence of anxiety among the general population during the COVID-19 pandemic reached 13.9% [ 14 ], which was higher than the rate of 5% before the outbreak [ 15 ]. In addition, it indicated that approximately 24.9% of college respondents in China manifested psychological anxiety symptoms during the COVID-19 outbreak, which was higher than previously reported as well [ 16 ]. There is usually a high prevalence of psychological symptoms among college students [ 17 ].…”
Section: Introductionmentioning
confidence: 78%
“…It was reported by a recent meta-analysis that the prevalence of anxiety among the general population during the COVID-19 pandemic reached 13.9% [ 14 ], which was higher than the rate of 5% before the outbreak [ 15 ]. In addition, it indicated that approximately 24.9% of college respondents in China manifested psychological anxiety symptoms during the COVID-19 outbreak, which was higher than previously reported as well [ 16 ]. There is usually a high prevalence of psychological symptoms among college students [ 17 ].…”
Section: Introductionmentioning
confidence: 78%
“…Specifically, if measures are applied to contain the epidemic, the presence of misinformation has a negative impact on their effectiveness. When protection, distancing measures, and detection and isolation policies are not applied, misinformation increases the infection and death rates even in the presence of a full lockdown [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Positive correlations between the fact of relying only on social media or non-scientific platforms and non-evidence-based behaviour were documented [ 63 ]. Wearing masks, social distancing and lockdown measures were fundamental elements in buffering the negative effects of misinformation: by not applying them, the virus was spread and deaths increased [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization (WHO) has warned of the risk of an “infodemic” wherein an overwhelming amount of circulating information discredits professional advice and prevents accurate information from reaching its target audience ( WHO, 2020 ). Some studies have found that people's exposure to misinformation may be associated with their violation of epidemic prevention regulations or resistance to vaccination ( Lee et al, 2020 ; Hornik et al, 2021 ; Loomba et al, 2021 ; Prandi and Primiero, 2020 ), and the sources of this misinformation can be traced back to political leadership in the government. For example, one study found the name of former U.S. president Donald Trump appeared in 37.9% of misinformation conversations about the COVID-19 pandemic ( Evanega et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%